Human body dynamics simulation and comfort evaluation of interhospital transport patients with different road conditions - Min Yao; Xiangjing Kong; Cui Pang; Yizhou Luo; Bao Zhang; Mei Li; Huang Huang; Liguo Zang (PLoS ONE, 2026)
Road unevenness has a significant impact on the comfort of patients during interhospital transport. Vibration is easy to cause dizziness, palpitation, tension, restlessness and other symptoms, and even cause secondary injuries to patients. Therefore, it is very important to analyze the vibration characteristics of human body and take care of vibration reduction. In this paper, the finite element technology, dynamic theory and experimental method are used to establish a “human-vehicle-road” coupling dynamic model, and the human dynamic response under different road conditions is simulated and analyzed. The results show that the human comfort is poor on bumpy road and continuous speed bumps; The vibration of different parts of human body is very different, and the head and sacrococcygeal vibration are the most obvious. Therefore, for patients with interhospital transport, vibration reduction nursing should be focused on the head and sacrococcygeal region. And a variable stiffness damping device is proposed, which has the functions of damping and limiting position. The simulation results show that the vibration reduction of head is more than 35%, and that of sacrococcygeal region is more than 30%. Therefore, the device is of great significance for improving the comfort of patients with interhospital transport.